Comparative anatomical study of uterus and oviducts of Nelore cows and heifers (Bos primigenius indicus) - Monteiro, Cristina Maria Rodrigues; Farias, Eduardo Cunha; Perri, Silvia Helena Venturoli; Souza, Wilson Machado de (Brazilian Journal of Veterinary Research and Animal Science, 2001)
Comparative anatomical results of lengths in uterine horns and oviducts of Nelore cows and heifers were investigated. Forty-five samples of each group of animals were used. The results showed that the medial length of the right and left uterine horns and oviducts of cows have not significative differences among them, being 26.0 cm to the right and left uterine horns, 17.6 cm to the right oviduct and 17.7 cm to the left one. The medial length of the right and left uterine horns and oviducts of heifers have not significative differences among them, being 14.6 cm to the right horn, 14.8 cm to the left one, 15.4 cm to the right oviduct and 15.2 cm to the left one. There is a significative difference in medial length of uterine horns among the groups of cows and heifers respectively, 26.01 cm and 14.72 cm. There is a significative difference in medial length of oviducts among cows and heifers, respectively 17.64 cm and 15.29 cm. The medial length of uterine horns in cows, 26.01 cm, is higher than the medial length of oviducts, 17.64 cm. In heifers the medial length of uterine horns, 14.72 cm, is smaller than the oviducts, 15.29 cm. When there is an enlargement of the medial length of uterine horns, there is an enlargement of oviducts in cows and do not in heifers.